Non-Linear EMG Parameters for Differential and Early Diagnostics of Parkinson’s Disease - Meigal, Alexander; Rissanen, Saara; Tarvainen, Mika; Airaksinen, Olavi; Kankaanpaa, Markku; Karjalainen, Pasi (Frontiers in Neurology, 2013)
The pre-clinical diagnostics is essential for management of Parkinson’s disease (PD). . Although PD has been studied intensively in the last decades, the pre-clinical indicators of that motor disorder have yet to be established. Several approaches were proposed but the definitive method is still lacking. Here we report on the non-linear characteristics of surface electromyogram (sEMG) and tremor acceleration as a possible diagnostic tool, and, in prospective, as a predictor for PD. Following this approach we calculated such nonlinear parameters of sEMG and accelerometer signal as correlation dimension, entropy and determinism. We found that the nonlinear parameters allowed discriminating some 85% of healthy controls from PD patients. Thus, this approach offers considerable potential for developing sEMG-based method for pre-clinical diagnostics of PD. However, non-linear parameters proved to be more reliable for the shaking form of PD, while diagnostics of the rigid form of PD using EMG remains an open question.